2017
DOI: 10.4028/www.scientific.net/msf.898.2205
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating of Copper on the Continuous Carbon Fibers

Abstract: Surface metallization of continuous carbon fibers (CFs) can improve the properties of the interface between the CFs and the metal matrix of the metal based composites. In this study, copper was coated on the surface of continuous CFs by electroplating in acidified copper sulfate electrolyte system. The effects of electroplating parameters such as current density, plating time, plating temperature and the pH value of electrolyte solution on the electroplating of the copper thin films on CFs were studied. The sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies on electrochemical oxidation of carbon fiber tows and electroplating carbon filaments demonstrated the successful surface treatment of noncontinuous carbon fibers in electrochemical cells. ,,,, Andideh and Esfandeh demonstrated that high oxidation of short carbon fiber tows can be achieved by nitric acid electrolysis, and some research groups demonstrated that relatively thick layers of nickel and copper coatings can be deposited on carbon filaments through electrolysis with nickel and copper salt solutions. Unfortunately, the former method can only treat one or a few carbon fiber tows at a time, and the latter method would damage carbon fibers during agitation of the solution (i.e., fibers would be broken up during stirring).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on electrochemical oxidation of carbon fiber tows and electroplating carbon filaments demonstrated the successful surface treatment of noncontinuous carbon fibers in electrochemical cells. ,,,, Andideh and Esfandeh demonstrated that high oxidation of short carbon fiber tows can be achieved by nitric acid electrolysis, and some research groups demonstrated that relatively thick layers of nickel and copper coatings can be deposited on carbon filaments through electrolysis with nickel and copper salt solutions. Unfortunately, the former method can only treat one or a few carbon fiber tows at a time, and the latter method would damage carbon fibers during agitation of the solution (i.e., fibers would be broken up during stirring).…”
Section: Resultsmentioning
confidence: 99%
“…Metal coating can be applied in different ways, such as electrode position, thermal evaporation, dipping and electroless plating [5,6]. Electroless plating has been recognized as one of the most attractive and best ways to apply coatings on none or semiconducting surface.…”
Section: Introductionmentioning
confidence: 99%
“…It is a process of deposing thin layer of metals, salts, oxides or any other compounds used in various industrial and technological applications. A redox reaction between a metal salt and a formaldehydes reduction in the same solution, a metal coating on surface can be formed in the absence of external current flow [5].…”
Section: Introductionmentioning
confidence: 99%